The Effectiveness of Ginger Oil Aromatherapy and Lemon Oil Aromatherapy on Reducing Emesis Gravidarum in Pregnant Women - Retno Palupi Yonni Siwi; Erma Retnaningtyas; Anggrawati Wulandari; Laily Dwi Jayati (Science Midwifery, 2022)
Emesis Gravidarum is caused by changes in liver glycogen and an increase in the hormone HCG. The purpose of this study was to determine the difference in the effectiveness of ginger oil aromatherapy and lemon oil aromatherapy on the reduction of emesis gravidarum in pregnant women. The design in this study is a quasy experiment with two groups of pretest posttest design with a sample size of 15 respondents per group. The sampling technique uses Simple Random Sampling while the data analysis test uses the Wilcoxon and Mann Whitney test. Before being given Ginger Oil aromatherapy as many as 9 respondents experienced moderate emesis. After being given ginger oil aromatherapy, 8 respondents did not experience emesis. Before being given Lemon Oil aromatherapy 9 respondents experienced mild emesis. After being given Lemon oil aromatherapy 12 respondents did not experience emesis. Analysis of the Wilcoxon test results there is an effect of giving Ginger Oil and Lemon Oil aromatherapy to reduce emesis gravidarum and the Mann Whitney test it is that Ginger Oil Aromatherapy is more effective in reducing nausea and vomiting compared to Aromatherapy Lemon Oil. Ginger oil contains essential oils that can be used to reduce nausea in pregnant women because the aroma produced is stronger.